SYNTHESIS OF ARTS IN DARIA MELNYKOVYCH-RYHTYTSKA’S LYRICS (on the material of collections “A thirst for the Real” (“Zhaha spravzhnioho”), “Magic of Fire” (“Mahiya vohniu”)) - Mashtaler, O. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes the problem of synthesis of arts in Dariya Ryhtytska’s lyric poetry. The work pays attention to understanding the processes of aesthetic space on the basis of verbal modeling of nonverbal arts. The ways of nascence of associative clutch of components of related arts, their combination, foremost, by the personality of an author-demiurge are revealed. The specifics of the writer’s artistic thinking, based on the crossbreeding of several arts, giving birth, as a result of this, to an original and integrally new poetic structure, are researched.